THE SOURCE DOMAIN OF JAVANESE WOMEN BODY SHAPE IN KYAI SESTRADILARAS MANUSCRIPT - Khoirur Rachmah (International Journal of Humanity Studies (IJHS), 2018)
This research entitled the source domain of Javanese women body shape in Kyai S?stradilaras manuscript. Kyai S?stradilaras manuscript is a manuscript about the image of beauty of Arjunas wives, including outward beauty and inner beauty. In this research, the analysis of the metaphorical and simile source domain of the body shape of Javanese women in Kyai Sestradilaras manuscript on outward beauty will be discussed. This research uses the metaphor theory initiated by Lakoff and Johnson (1980), the theory of source domain according to Haley (1980), and simile theory according to Abrams through Marsono (1996). The method used in this research is descriptive qualitative method. Implementation of this method consists of three stages, data collection methods, data analysis methods, and presentation of data analysis result method. The data in this research are obtained from the written source. The results of the research are the metaphorical and simile source domain of the body shape of Javanese women in Kyai S?stradilas manuscript. The source domains are 1) the moonlit sky to illustrate the beauty of a woman's eyes, 2) the sky to describe the beauty of a woman's face, 3) the dahlia flower to describe the beauty of a woman's face, 4) the fennel leaves to describe the beauty of a woman's face, 5) pomegranate to describe the beauty of a woman's face, 6) the moon to describe the beauty of a woman's skin, 7) golden money ray to describe the beauty of a woman's skin, 8) ivory palm to describe the beauty of a woman's breasts, and 9) cempaka flowers to illustrate the beauty of a woman's breasts.